Algae as Bioindicators of Aquatic Pollution - Ahmed, Shahnawaz (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 11 No 1&2 (2024): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2024)
The assessment of water quality in aquatic ecosystems is of paramount importance in the context of environmental preservation and human health. Algae have emerged as invaluable bioindicators for monitoring aquatic pollution due to their sensitivity to environmental changes and rapid response. This article provides a comprehensive overview of the advancements and challenges associated with using algae as bioindicators of aquatic pollution. Recent developments in algal research have facilitated the identification of specific algal species that are highly responsive to various pollutants, enabling precise and efficient pollution assessment. Cutting-edge technologies, such as DNA sequencing and remote sensing, have enhanced our ability to monitor algae populations in real-time. Furthermore, the integration of algal data with sophisticated statistical models has improved the accuracy of pollution assessments, making them more reliable for regulatory and conservation purposes. Despite these advancements, challenges remain, including the standardization of bioindicator protocols, data interpretation, and the potential influence of multiple stressors on algal communities. The article discusses the need for interdisciplinary collaboration, ongoing research, and policy support to address these challenges and further enhance the role of algae as bioindicators in safeguarding our precious aquatic ecosystems.